2017
DOI: 10.1017/s0007114517002331
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women of South Asian ethnicity in Canada have substantially lower vitamin B12status compared with pregnant women of European ethnicity

Abstract: Maternal vitamin B12 (B12) status has been inversely associated with adverse pregnancy outcomes and positively with fetal growth and infant development. South Asians, Canada's largest ethnic minority, are prone to B12 deficiency. Yet, data are lacking on B12 status in South Asian pregnant women in North America. We sought to determine B12 status, using multiple biomarkers, in 1st and 2nd trimester pregnant women of South Asian and, for comparison, European ethnicity living in Vancouver, Canada. In this retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 73 publications
(120 reference statements)
1
5
0
Order By: Relevance
“…In accordance with this MMA and Hcy levels have been reported to increase by late pregnancy [32,33]. A Canadian study found that 10% of women are vitamin B 12 deficient in early pregnancy [34], and several consecutive studies have confirmed similar findings or even higher frequencies for vitamin B 12 deficiency in pregnancy of up to 30% in different populations and ethnicities [31,[35][36][37][38]. This underscores the relevance of this condition for NBS programmes and stresses that also in caregivers of pregnant women awareness for B 12 deficiency should be increased.…”
Section: Discussionsupporting
confidence: 54%
“…In accordance with this MMA and Hcy levels have been reported to increase by late pregnancy [32,33]. A Canadian study found that 10% of women are vitamin B 12 deficient in early pregnancy [34], and several consecutive studies have confirmed similar findings or even higher frequencies for vitamin B 12 deficiency in pregnancy of up to 30% in different populations and ethnicities [31,[35][36][37][38]. This underscores the relevance of this condition for NBS programmes and stresses that also in caregivers of pregnant women awareness for B 12 deficiency should be increased.…”
Section: Discussionsupporting
confidence: 54%
“…Wnt signaling has been reported to be disrupted in the developing cerebellum of the offspring of vitamin B 12 – and folate-deficient female rats 78 and is associated with long-term disabilities of behavior and memory 79 . Ethnic differences in vitamin B 12 levels have been observed in pregnancy, possibly related to differences in intake of animal-derived foods 80 . Children born to mothers with normal to high folate levels and low serum vitamin B 12 values have higher truncal adiposity and insulin resistance, 81 which may influence long-term risk of development of type 2 diabetes and cardiovascular disease 82, 83.…”
Section: Consequences Of Maternal and Infant Low B12 Statusmentioning
confidence: 99%
“…Consideration of ethnicity as an effect modifier in biomarker concentration and potential risk marker should be carefully evaluated. In our work on maternal micronutrient status in pregnant women of South Asian ethnicity residing in British Columbia, Canada, we showed that women of South Asian ethnicity have substantially lower vitamin B 12 status, as shown by the significantly lower serum total B 12 and holotranscobalamin concentration and higher serum MMA concentration, compared with women of European ethnicity in early pregnancy ( 53 ) . There was no significant difference in tHcy concentration between the two ethnic groups; however, this can likely be explained by the high folate status in Canadian pregnant women including our cohort with a median serum folate concentration of about 65 nmol/l ( 53 ) and with folate being the main determinant of tHcy concentration ( 56 ) .…”
Section: Influencing Factors On Biomarker Variability and Cut-offsmentioning
confidence: 79%
“…With respect to the routinely applied biomarker serum total vitamin B 12 and related cut-off, there is a general concern that the rate of B 12 deficiency is overestimated during pregnancy because of a natural decrease in serum total B 12 concentrations across trimesters of pregnancy ( 52 54 ) , potentially attributable to pregnancy-related haemodilution, changes in glomerular filtration rate, and the preferential unidirectional transport of nutrients to the developing fetus. Also serum holotranscobalamin, the biomarker reflecting the portion of vitamin B 12 available to tissues and alternative direct B 12 indicator, significantly decreased between first and second trimester of pregnancy ( 53 ) , while the functional biomarker plasma MMA increased between the first and second ( 53 ) , and between second and third trimester ( 55 ) . As for cut-offs for all other age and population groups, a defined clinical and/or physiologic endpoint is required to validate cut-offs for the reliable definition of maternal vitamin B 12 adequacy and thereby for achieving both maternal health and optimal fetal growth and development.…”
Section: Influencing Factors On Biomarker Variability and Cut-offsmentioning
confidence: 99%